2023
DOI: 10.1021/acs.jmedchem.2c01410
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Indazole Chemotypes as Isoform-Selective JNK3 Inhibitors for the Treatment of Parkinson’s Disease

Abstract: c-Jun N-terminal kinases (JNKs) are involved in the pathogenesis of various diseases. In particular, JNK3 and not JNK1/2 is primarily expressed in the brain and plays a key role in mediating neurodegenerative diseases like Parkinson's disease (PD). Due to the sequence similarity of JNK isoforms, developing isoform-selective JNK3 inhibitors to evaluate their biological functions and therapeutic potential in PD has become a challenge. Herein, docking-based virtual screening and structure−activity relationship st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…According to X-ray crystallography, the indazole-aminopyrimidine compound binds to JNK1b (PDB: 4HYU) and interacted via two hydrogen bonds with the amino acid backbones of the hinge region [8]. A co-crystal structure of JNK3 (PDB: 3KVX) and the aminopyridine ligand revealed that it was positioned within the adenosine-binding region, and the morpholino substituent was positioned within the hydrophilic sugar pocket [9]. It was also observed in a co-crystal structure of JNK3 (PDB: 4Y5H) that two hydrogen bonds with Met149 were formed at the adenine-binding site [10].…”
Section: Introductionmentioning
confidence: 99%
“…According to X-ray crystallography, the indazole-aminopyrimidine compound binds to JNK1b (PDB: 4HYU) and interacted via two hydrogen bonds with the amino acid backbones of the hinge region [8]. A co-crystal structure of JNK3 (PDB: 3KVX) and the aminopyridine ligand revealed that it was positioned within the adenosine-binding region, and the morpholino substituent was positioned within the hydrophilic sugar pocket [9]. It was also observed in a co-crystal structure of JNK3 (PDB: 4Y5H) that two hydrogen bonds with Met149 were formed at the adenine-binding site [10].…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson’s disease is the second most prevalent debilitating neurological disorder, affecting 3% of the worldwide population over the age of 65. , With aging of the population, a steady and irreversible depletion of dopaminergic neurons in substantia nigra pars compacta leads to an imbalance in the concentration of dopamine in the striatum, and therefore, the accurate management of Parkinson’s disease becomes a challenging task for neurologists. , The cause of PD is multifactorial involving different mechanistic pathways such as oxidative stress, neuroinflammation, apoptosis, mitochondrial dysfunction, and so forth . Usually, Parkinson’s patients experience a variety of motor symptoms owing to the brain’s dopamine depletion, including hyperactivity disorder, schizophrenia, static tremor, flexed posture, freezing of gait, rigidity, and so forth …”
Section: Introductionmentioning
confidence: 99%
“…More than 100 JNK inhibitors have been identified, with some even evaluated in clinical trials, yet fewer than ten JNK3-selective inhibitors have been reported [ 44 , 45 , 46 , 47 ]. Tryptanthrin (TRYP) (indolo[2,1- b ]quinazolin-6,12-dione) is an alkaloid that can be isolated from higher plants and several marine organisms (for a review, see [ 48 ]).…”
Section: Introductionmentioning
confidence: 99%